FTO-Dependent N6-Methyladenosine Regulates Cardiac Function During Remodeling and Repair. Issue 4 (22nd January 2019) - Mathiyalagan, Prabhu; Adamiak, Marta; Mayourian, Joshua; Sassi, Yassine; Liang, Yaxuan; Agarwal, Neha; Jha, Divya; Zhang, Shihong; Kohlbrenner, Erik; Chepurko, Elena; Chen, Jiqiu; Trivieri, Maria G.; et al.
Abstract : Background: Despite its functional importance in various fundamental bioprocesses, studies of N 6 -methyladenosine (m6A) in the heart are lacking. Here, we show that the FTO (fat mass and obesity-associated protein), an m6A demethylase, plays a critical role in cardiac contractile function during homeostasis, remodeling, and regeneration. Methods: We used clinical human samples, preclinical pig and mouse models, and primary cardiomyocyte cell cultures to study the functional role of m6A and FTO in the heart and in cardiomyocytes. We modulated expression of FTO by using adeno-associated virus serotype 9 (in vivo), adenovirus (both in vivo and in vitro), and small interfering RNAs (in vitro) to study its function in regulating cardiomyocyte m6A, calcium dynamics and contractility, and cardiac function postischemia. We performed methylated (m6A) RNA immunoprecipitation sequencing to map transcriptome-wide m6A, and methylated (m6A) RNA immunoprecipitation quantitative polymerase chain reaction assays to map and validate m6A in individual transcripts, in healthy and failing hearts, and in myocytes. Results: We discovered that FTO has decreased expression in failing mammalian hearts and hypoxic cardiomyocytes, thereby increasing m6A in RNA and decreasing cardiomyocyte contractile function. Improving expression of FTO in failing mouse hearts attenuated the ischemia-induced increase in m6A and decrease in cardiac contractile function. This is performed by the demethylation activity of FTO, which selectively demethylates cardiac contractile transcripts, thus preventing their degradation and improving their protein expression under ischemia. In addition, we demonstrate that FTO overexpression in mouse models of myocardial infarction decreased fibrosis and enhanced angiogenesis. Conclusions: Collectively, our study demonstrates the functional importance of the FTO-dependent cardiac m6A methylome in cardiac contraction during heart failure and provides a novel mechanistic insight into the therapeutic mechanisms of FTO. Abstract : Supplemental Digital Content is available in the text.